Analisis Pengetahuan dan Peran Mahasiswa dalam Mengurangi Pergaulan Bebas dan Aborsi di Lingkungan FMIPA: Studi Kasus Pendidikan Biologi Kelas A 2024 - Sidauruk, Bertha Angelina; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Putri, Nadilla; Syahru, Zahara Ain Nur; Hasni, Asih Maulida; Wati, Diana Vera; Br Ginting, Nurlela (VISA: Journal of Vision and Ideas, 2024)
Promiscuity and abortion among university students have become increasingly worrying issues in recent years. Abortion is an act of miscarriage or termination of pregnancy before the womb reaches 22 weeks or when the fetus weighs less than 500 grams that can occur naturally, known as spontaneous abortion (miscarriage). The method used in this research is descriptive qualitative with data collection techniques are observation, interviews, and documentation. The number of respondents to be studied is 10 respondents. This study aims to analyze the level of knowledge of students regarding their role in reducing these negative behaviors in the Faculty of Mathematics and Natural Sciences (FMIPA). Based on data analysis, the findings generated in this study are that from all participants, students generally perceive promiscuity as a violation of norms and adversely affecting their mental and social health. Family, curiosity, and environmental factors play an important role in encouraging or preventing promiscuity.